Revenue Diversification, Capital Budgeting Practices and Financial Sustainability: The Moderating Role of Sustainability Audits - Marwa Nyahende Kesanta; Victoria Makuya; Athuman Makona (SEISENSE (PRIVATE) LIMITED, 2026)
Purpose: This study is anchored on the Resource-Based View and Modern Portfolio theories to investigate the impact of revenue diversification (RD) and capital budgeting practices (CBP) on financial sustainability (FS), moderated by sustainability audits (SA).Design/Methodology: Data were collected from 228 managers using a cross-sectional research design and a questionnaire. Data analysis were through Partial least squares structural equation modeling (PLS-SEM). Findings: Analysis reveals that RD and CBP significantly and positively drive FS, though RD demonstrates a greater effect. SA moderated positively the association between the RD and FS, but negatively on the CBP and FS linkage.Practical Implications: The study’s findings inform the management and policymakers of Savings and Credit Cooperative Organisations (SACCOS) in recognising and prioritising SA, RD, and CBP in their decision-making and planning processes to achieve financial success. They should embrace regular investment training, investment diversification, and designate a dedicated unit to manage revenue diversification and capital budgeting practices to achieve FS.